A Review of Resilience Enhancement Techniques for Cyber-Physical Systems - Gomez-Cabrera Alain; Ponciano Jorge Escamilla-Ambrosio; Mohammad Abdullah Al Faruque (IEEE Access)
Cyber-physical systems (CPS) integrate computational and physical components, enabling interaction between the digital and physical worlds. As CPS become increasingly prevalent across various domains, ensuring their resilience against disturbances and anomalies, stemming from both cyberattacks and system faults, has become a critical concern. These systems are exposed to risks that can jeopardize safety, reliability, and operational continuity. This study presents a comprehensive and structured review of state-of-the-art resilience enhancement techniques in CPS, with a focus on key aspects that define the concept of resilience adopted in this work: anomaly detection, attack mitigation, fault recovery, and system reconfiguration. We analyze and classify recent approaches such as robust control, fault-tolerant architectures, and secure state estimation, illustrating how these methods address threats like cyber-physical attacks and hardware failures. Our main contribution lies in identifying current gaps within existing resilience frameworks, particularly the need for integrated and adaptive solutions. By synthesizing insights across disciplines, this review serves as a foundational reference for researchers and practitioners aiming to design robust and secure CPS for adversarial environments.